Correction: Corrigendum: Engineering and optimising deaminase fusions for genome editing - Luhan Yang (Nature Portfolio, 2017)
Nature Communications 7: Article number: 13330 (2016); Published 2 November 2016; Updated 9 October 2017. The original version of this Article contained an error in the email address of the corresponding author George Church. The correct email is gchurch@genetics.med.harvard.edu. The error has been corrected in the HTML and PDF versions of the Article.